The death penalty in China : policy, practice, and reform - Liang, Bin, 1972-; Lu, Hong, 1966-; Hood, Roger, 1936- (New York : Columbia University Press, 2016)
Featuring experts from Europe, Australia, Japan, China, and the United States, this comparative study follows changes in the theory and policy of China's death penalty from the Mao era (1949-1979) through the Deng era (1980-1997) and up to the present day.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 18, 2016).
Keywords: Capital punishment -- China; Criminal justice, Administration of -- China; True Crime; China; Social services & welfare, criminology; Penology & punishment; Sentencing & punishment